From Awareness To Adoption: Behavioral Of ICT Adoption To Quality Reporting - Aldila Dinanti; Indira Januarti; Rr. Sri Handayani (Jurnal Akuntansi, 2025)
This article provides further knowledge on the adoption of ICT as an efficient and effective provider of accounting information through factors within the technology-organization and environment (TOE) framework. Data were collected using a survey from 129 owners and financial managers of SMEs under an SME association in Banyumas, Central Java. The results showed that ICT adoption in SMEs through the TOE framework is driven by technology playing a major role in driving ICT adoption, while environmental factors can be a constraint. Meanwhile, the contribution of organizational factors tends to be insignificant in this context. The proposed model will be useful for IS vendors in making investment decisions and devising marketing programs that appeal to non-adopters. This is because non-adopters face more adoption challenges than adopters and tend to be less loyal.